2014
DOI: 10.2737/rmrs-rn-69
|View full text |Cite
|
Sign up to set email alerts
|

Post-fire erosion control mulches alter belowground processes and nitrate reductase activity of a perennial forb, heartleaf arnica (Arnica cordifolia)

Abstract: Four years post-wildfire, we measured soil and plant properties on hillslopes treated with two different mulches (agricultural wheat straw and wood strands) and a control (unmulched, but burned

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 39 publications
1
7
0
Order By: Relevance
“…Inorganic soil N declines as it is immobilized within wood mulch or similar high C, low N soil amendments [ 53 , 57 ]. The low IER nitrate we reported in mulched plots ( Figure 1 ) is similar to reduced post-fire nitrate losses measured under wood mulch elsewhere [ 58 , 59 ]. In another study in Colorado forests, thick mulch reduced nitrate to a greater extent than thin mulch (7.5 versus 15 cm [ 60 ]).…”
Section: Discussionsupporting
confidence: 86%
“…Inorganic soil N declines as it is immobilized within wood mulch or similar high C, low N soil amendments [ 53 , 57 ]. The low IER nitrate we reported in mulched plots ( Figure 1 ) is similar to reduced post-fire nitrate losses measured under wood mulch elsewhere [ 58 , 59 ]. In another study in Colorado forests, thick mulch reduced nitrate to a greater extent than thin mulch (7.5 versus 15 cm [ 60 ]).…”
Section: Discussionsupporting
confidence: 86%
“…By adding OM and improving soil temperature and water holding conditions, organic mulches should increase soil microbial activity in burned soils, but mulching studies have given mixed results. Berryman et al (2014a) found a positive, but variable, effect of different soil mulches on wood stake mass loss after a high-severity wildfire in Colorado. In contrast, Fontúrbel et al (2012) and Lombao et al (2013) reported that applying a straw mulch after a prescribed low-severity fire in Spain had no impact on soil microbial biomass, microbial diversity, and soil respiration rates.…”
Section: Introductionmentioning
confidence: 91%
“…Organic mulches are often applied to the soil surface to reduce post-fire erosion by improving water-holding capacity and infiltration (Foltz and Wagenbrenner, 2010;Robichaud et al, 2013;Lucas-Borja et al, 2018a), and to help reestablish vegetation by lowering soil temperature, reducing surface water evaporation, and increasing soil OM content (Berryman et al, 2014a;Prats et al, 2016). Agricultural residues (e.g., wheat straw and hay) are often used, but they are susceptible to wind erosion and often contain seeds of non-native vegetation (Beyers, 2004;Bautista et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The surge of new vegetation growth in the first year may seem incongruent with the initial burn severity classification due to a boost in plant-available nitrogen (Stephan et al 2012) and nutrients remaining in the ash layer (Neary et al 1999); thus, it is important to monitor vegetation and soil recovery characteristics over time (Sankey et al 2013;Berryman et al 2014). The resilience of the ecosystem to the fire disturbance depends on specific conditions of the pre-fire environment such as vegetation type and density, and forest health such as drought or insect kill, taken into consideration with the scale and intensity of effects of the fire on the vegetation and soil (Idris et al 2005;Schoennagel et al 2008;Bowman et al 2009;Perry et al 2011).…”
Section: Introductionmentioning
confidence: 99%